137Cs contamination and its vertical distribution in the curonian spit soil - Morkūniene, Rasa; Valuntaite, Vaida; Girgždys, Aloyzas; Astrauskiene, Nijole (Journal of Environmental Engineering and Landscape Management, 2005)
In 2003–2004 soil depthprofile sampling was carried out at Juodkrantein the Curonian Spit. The activity concentrations of anthropogenic radionuclide 137Cs in soil samples from the terrestrial and coastal environment of the Curonian Spit were determined and a study of their distribution was performed. The range of activity concentrations of accumulated deposits of 137Cs in a 0–30 cm soil layer is 0,2–370,9 Bq · kg−1 and 2,2–11,2 Bq · kg−1 in samples of the forest soil and beach sand, respectively. Soil depth profiles display higher activity concentration levels in their upper layer of the forest soil and insignificant variations of lower activity concentrations in the surf zone‐the dune ecosystem. Tarša 137Cs ir jo vertikalusis pasiskirstymas Kuršių nerijos dirvožemyje Santrauka. Nustatytas dirbtinės kilmės radionuklido 137Cs savitasis aktyvumas kranto smėlyje bei miško dirvožemyje, tam tikslui atlikta 2003–2004 m. Kuršių nerijoje ties Juodkrante paimtų grunto bandinių analizė 137Cs savitasis aktyvumas miško dirvožemio 0–30 cm sluoksnyje kito nuo 0,2 iki 370,9 Bq · kg−1, o kranto ir kopų smėlyje – nuo 2,2 iki 11,2 Bq · kg−1. Didžiausias radionuklido savitasis aktyvumas nustatytas paviršiniame 0–5 cm miško dirvožemio sluoksnyje, gilesniuose kranto bei kopų smėlio sluoksniuose jis pakito neženkliai. Reikšminiai žodžiai: Kuršių nerija, dirvožemis, radionuklidas, 137Cs. First Published Online: 14 Oct 2010